Retraction: Hamadouche NA, Sadi N, Kharoubi O, Slimani M, Aoues A. The protective effect of vitamin E against genotoxicity of lead acetate intraperitoneal administration in male rat. Arch biol sci. 2013;65(4):1435-45. DOI: 10.2298/ABS1304435H - Editorial (Archives of Biological Sciences, 2015)
This is a notice of retraction of the article: The protective effect of vitamin E against genotoxicity of lead acetate intraperitoneal administration in male rat, published in the Archives of Biological Sciences in 2013, Vol. 65, Issue 4. The Editor-in-Chief has been informed that this paper is a duplicate of an earlier paper: Hamadouche NA, Sadi N, Kharoubi O, Slimani M, Aoues A. The protective effect of vitamin E against genotoxicity of lead acetate intraperitoneal administration in male rat. Notulae scientia biologicae. 2013;5(4):412-9. This claim is correct and the results have already been presented in the article published earlier. After confirmation of this fact, the Editor-in-Chief of the Archives of Biological Sciences has decided to retract the paper immediately. We apologize for this error. Link to the retracted article 10.2298/ABS1304435H